An analysis of why SAPPI Limited had to issue foreign denominated debt - Weimann, Dylan (Department of Finance and Tax, 2017)
SAPPI Limited ("SAPPI") is a company that was established in South Africa in the 1930's and has grown into a global player in the paper and pulp industry, as well as the chemical cellulose industry. Historical financing decisions made in the growth phases of the company's life cycle left it with the need to refinance debt obligations payable in the early 2010's. In order to meet these obligations, four callable bonds with high coupon rates denominated in Euro and US Dollar were issued in 2011 and 2012 below investment grade. This study examines the cost at which these high yield bonds were issued by SAPPI and discusses the potential reasoning behind the decisions made by SAPPI in the process to obtain further financing. Financing solutions within the South African market are discussed with the conclusion that the South African listed high yield corporate bond market was not adequate for SAPPI, given its credit rating being below investment grade and the value of funding required. In addition, SAPPI's exposure to foreign currencies through global operations made the Euro and US Dollar denominated bond issues favourable to the business. To illustrate the cost of the bonds issued in both Euro and US Dollar, the second part of this study consists of an analysis of the option‐adjusted spreads at which these bonds were issued. Our analysis involved taking into account the probability of the call provisions being exercised by SAPPI at the date of issue through a detailed application of the option‐adjusted spread methodology and the use of a recombining binomial lattice. Through a quantitative example of the process followed and a discussion of the spreads determined, we indicate the true cost at which finance was obtained by SAPPI for each bond issued. A brief discussion on the hedging decisions taken by SAPPI management on the issuance of the debt has also been included. Furthermore, the retrospective performance of the foreign exchange hedging decisions made have been assessed through movements in global financial markets from the time hedging decisions were enacted up until 30 September 2015.